2020
DOI: 10.1515/polyeng-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

Polysulfone nanofiltration membranes enriched with functionalized graphene oxide for dye removal from wastewater

Abstract: Composite-nanofiltration membranes based on polysulfone (PSU) and functionalized graphene oxide (f-GO) were prepared for dye removal from aqueous media. Graphene oxide (GO) was introduced to enhance the performance of these membranes. GO was functionalized using an aminated heterocyclic compound, namely 6-amino-4-(4-nitrophenyl)-3-methyl-4-phenyl-4,7-dihydro-1H-pyrazolo-[3,4-b]pyridine-5carbonitrile. The f-GO was incorporated into the PSU membrane matrix in different weight ratios (0.25, 0.5, 1, 2 and 4 wt %).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Previous research suggested that acrylic fibers comprise at least 85% to 90% acrylonitrile, with the remainder comprising the acrylic-based monomer known as acrylic ester or acid [ 24 ]. Moreover, the wide peak at 3418 cm −1 could be attributed to absorbed water and the OH group for the additives of the polymer, whereas the peaks at 2860 and 2933 cm −1 correspond to the stretching of CH and CH 2 , respectively [ 46 ]. The band of 1230 cm −1 relates to the bending vibration CH 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggested that acrylic fibers comprise at least 85% to 90% acrylonitrile, with the remainder comprising the acrylic-based monomer known as acrylic ester or acid [ 24 ]. Moreover, the wide peak at 3418 cm −1 could be attributed to absorbed water and the OH group for the additives of the polymer, whereas the peaks at 2860 and 2933 cm −1 correspond to the stretching of CH and CH 2 , respectively [ 46 ]. The band of 1230 cm −1 relates to the bending vibration CH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 12 d shows that the AF blank membrane cross-section contained a macro-void-like structure with numerous large pores. These indicate the spontaneous de-mixing during the immersion of the membrane solution in the coagulation bath (phase inversion technique) [ 46 , 47 ]. The cross-section of AF-U and AF-S membranes ( Figure 12 e,f) contains a similar structure with no obvious aggregation of the microparticles of algae at these magnifications.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose acetate-Ulva fasciata composite polymer membrane (CA-U membrane) was prepared via an immersionprecipitation method [37,38]. Firstly, a blank cellulose acetate (CA) (Aldrich, 40% acetyl content) polymer was prepared by dissolving the cellulose acetate powder in acetone (20 wt%) (El-Nassar company, Egypt) in a closed conical flask with stirring at room temperature till complete solubility.…”
Section: Preparation Of Cellulose Acetate-ulva Fasciata Composite Membranementioning
confidence: 99%
“…Dye removal can be achieved through various routes comprising adsorption [18], filtration [19] or catalyzed degradation [20,21]. Herein, we focus on the catalyzed degradation of MO in aqueous solution in order to assess the catalytic activity of the actual CuNi-decorated biochar.…”
Section: Potential Environmental Remediation Application: Heterogeneous Catalyzed Degradation Of Methyl Orange (Mo)mentioning
confidence: 99%